2014
DOI: 10.4236/ajac.2014.51005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soya Lecithin on Solubilization and Biodegradation of Pentachlorophenol by <i>Anthracophyllum discolor</i>

Abstract: The effect of soya lecithin (SL) on solubilization and biodegradation of pentachlorophenol (PCP) by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, it was found that A. parasiticus growth and spore germination was greater in the presence of Mcapsules and Mcapsules/FA, compared with those in buffer acetate control. This effect can be attributed to the presence of lecithin in the capsules, since it is reported that lecithin accelerates the growth of fungus, such as in Anthracophyllum discolor, which uses it as a carbon source (Bustamante, Rubilar, & Diez, 2014). The addition of FA in Nparticles and Mparticles potentiated its inhibitory effect, compared with the matrices without FA.…”
Section: Radial Growthmentioning
confidence: 98%
“…Furthermore, it was found that A. parasiticus growth and spore germination was greater in the presence of Mcapsules and Mcapsules/FA, compared with those in buffer acetate control. This effect can be attributed to the presence of lecithin in the capsules, since it is reported that lecithin accelerates the growth of fungus, such as in Anthracophyllum discolor, which uses it as a carbon source (Bustamante, Rubilar, & Diez, 2014). The addition of FA in Nparticles and Mparticles potentiated its inhibitory effect, compared with the matrices without FA.…”
Section: Radial Growthmentioning
confidence: 98%
“…The aggressive wood rot fungi which are widely spread in the world, thanks to their enzymes it could be an excellent candidate for direct biodegradation of pollutants. Most of the current research focused mostly on the activities of these ligninolytic enzymes to understand the enzymatic mechanism of PCP degradation in wood rot fungi, and lignolytic enzymes LiP, MnP and Lac were found to play important role in organic pollutant degradation [7][8][9][10][11]. Usually, when fungi increase their enzymatic activity, they showed a higher degradation of PCP.…”
Section: Ligninolytic Enzymes Activitiesmentioning
confidence: 99%
“…Extracellular ligninolytic enzymes and cytochrome P450 enzymes of wood rot fungi have been reported to be responsible for organic pollutants degradation. Phanerochaete chrysosporium [4], Phanerochaete sordida [5], Trametes hirsuta [6], Trametes versicolor [7], Lentinula edodes [8], Bjerkandera adusta [9], Anthracophyllum discolor [10], Laetiporus cincinnatus, Fomes fomentarius, Ganoderma applantum and Pleurotus ostreatus [11] are some of the wood rot fungi that show the ability to degrade PCP, and methylation and dechlorination are common reactions in transformation of PCP by these fungi. Among them, P. chrysosporium and T. versicolor have been the most widely used wood rot fungi for PCP degradation.…”
Section: Introductionmentioning
confidence: 99%